Solutions for Improving the Efficiency of Sea Import Freight Forwarding Procedure for Less than Container Load Cargo at Vietlink Group Company Limited - Dinh, Quan Thuy (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Logistics and Digital Supply Chain Management; 2021-2025.